Liquid Organic Fertilizer Application Test on the Early Growth of Ginger Plants (Zingiber officinale) - Herawati, Jajuk; Widya, Surya Ari; Sa'adah, Tatuk Tojibatus; Dhinata, Yhogga Pratama (Journal of Applied Plant Technology, 2025)
The research consists of two stages, the first being the development of LOF production from water hyacinth and banana peel applied to ginger plants. The purpose of the study is to determine the extent to which the application of liquid organic fertilizer (LOF) can enhance the early growth of ginger plants. The second is the cultivation of ginger plants by applying various types of LOF compared to ginger plants without LOF application. The research was conducted from the end of August to November 2025 in Banjar Poh Village, Sidoarjo District, Sidoarjo Regency.  Research hypothesis: (1) It is suspected that different LOF applications will result in different early growth in ginger plants, (2) it is suspected that the use of banana peel LOF provides better early growth in ginger plants compared to other treatments. The study used a Randomized Block Design (RBD) method with one factor consisting of 4 treatments. The treatment involved the provision of types of LOF, namely P1 = without LOF; P2 = LOF water hyacinth; and P3 = LOF banana peel P4 = EM4 (Effective Microorganisms 4). Each treatment was repeated 3 times, and each repetition had 3 plant samples. Observations of the early growth of ginger plants include shoot height, number of shoots, and number of leaves. The obtained data were analyzed using analysis of variance, and if there were significant differences, it was followed by the Least Significant Difference (LSD) test at 5%.